Hulumtime gjuhësore lidhur me përzgjedhjen e formave gramatikore të fëmijëve emigrantë - Grillo, Helena (Seminari Ndërkombëtar për Gjuhën, Letërsinë dhe Kulturën Shqiptare, 2018)
The development of demographic movement after the ’90 was associated with changes in language and culture. According to the statistics of the office of Immigration a great number of Albanians have moved and live in the countries of Western Europe, USA, Canada, England etc.The necessity that comes in this phase in the view of language researchers, out of the political and ethnical developments is to preserve the Albanian language of the second generation, in children of immigrants that moved in these years. Their Albanian changes its status, being a second language, very often is not institutionalized. It comes as a need the development of linguistic politics and mechanisms in order for the Albanian language to be saved and preserved from the Albanians that live abroad. Taking into consideration the challenges and difficulties encountered during the collection of data we applied the observation and oriented conversation for the variety of the spoken language and questionnaires with real examples for the variation of the written language. The selection of the sample was conditioned by the country, in Greece we observed the children of immigrants that learn the language as a second language in extracurricular classes with specializes Albanian language teachers. In Italy the selection was more casual, and the measurements were realized only for the variety of the spoken language. Later we studied the conditioning of the selection of the grammar forms from the linguistic and non linguistic factors, and the data was analyzed statistically.